Heterologous Chimeric Construct Comprising a Modified Bacterial Superantigen and a Cruzipain Domain Confers Protection Against Trypanosoma cruzi Infection - Antonoglou, María Belén; Sánchez Alberti, Andrés; Redolfi, Daniela María; Bivona, Augusto Ernesto; Fernández Lynch, María Julieta; Noli Truant, Sofía; Sarratea, María Belén; Iannantuono López, Laura Valeria; Malchiodi, Emilio Luis; Fernández, Marisa Mariel (Frontiers in Immunology, 2020)
Chagas disease is an endemic chronic parasitosis in Latin America affecting more than 7 million people. Around 100 million people are currently at risk of acquiring the infection; however, no effective vaccine has been developed yet. Trypanosoma cruzi is the etiological agent of this parasitosis and as an intracellular protozoan it can reside within different tissues, mainly muscle cells, evading host immunity and allowing progression towards the chronic stage of the disease. Considering this intracellular parasitism triggers strong cellular immunity that, besides being necessary to limit infection, is not sufficient to eradicate the parasite from tissues, a differential immune response is required and new strategies for vaccines against Chagas disease need to be explored. In this work, we designed, cloned and expressed a chimeric molecule, named NCz-SEGN24A, comprising a parasite antigen, the N-terminal domain of the major cysteine protease of T. cruzi, cruzipain (Nt-Cz), and a non-toxic form of the staphylococcal superantigen (SAg) G, SEG, with the residue Asn24 mutated to Ala (N24A). The mutant SAg SEGN24A, retains its ability to trigger classical activation of macrophages without inducing T cell apoptosis. To evaluate, as a proof of concept, the immunogenicity and efficacy of the chimeric immunogen versus its individual antigens, C3H mice were immunized intramuscularly with NCz-SEGN24A co-adjuvanted with CpG-ODN, or the recombinant proteins Nt-Cz plus SEGN24A with the same adjuvant. Vaccinated mice significantly produced Nt-Cz-specific IgG titers after immunization and developed higher IgG2a than IgG1 titers. Specific cell-mediated immunity was assessed by in-vivo DTH and significant responses were obtained. To assess protection, mice were challenged with trypomastigotes of T. cruzi. Both schemes reduced the parasite load throughout the acute phase, but only mice immunized with NCz-SEGN24A showed significant differences against control; moreover, these mice maintained 100% survival. These results encourage testing mutated superantigens fused to specific antigens as immune modulators against pathogens.